2013
DOI: 10.1097/mao.0b013e318289844c
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Findings in Acute Facial Palsy in Children

Abstract: Microbiologic etiology association of pediatric facial palsy could frequently be confirmed. Borreliosis was the single most common cause; hence, cerebrospinal fluid sampling is recommended for all pediatric cases in endemic areas. Varicella zoster virus accounted for 11% of the cases, being the second most common factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…Furthermore, some of the patients might have been infected by neurotropic agents not tested for in our present study, i.e. Epstein-Barr virus (EBV), human herpes virus (HHV) 6 or 7, cytomegal virus (CMV), mycoplasma or influenza A or B [18]. Different refined method for detection of different causative agents in the central nervous system (CNS) has been in focus by Huttunen et al [35].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, some of the patients might have been infected by neurotropic agents not tested for in our present study, i.e. Epstein-Barr virus (EBV), human herpes virus (HHV) 6 or 7, cytomegal virus (CMV), mycoplasma or influenza A or B [18]. Different refined method for detection of different causative agents in the central nervous system (CNS) has been in focus by Huttunen et al [35].…”
Section: Discussionmentioning
confidence: 95%
“…Acute facial nerve palsy or subacute meningitis are major neurological manifestations in LNB [12] [13]. However, facial nerve palsy may also be associated with viral infection, such as an acute or reactivated herpes simplex virus (HSV) infection or a reactivated varicella zoster virus (VZV), even when detectable vesicles or other clinical manifestations of viral infection are absent [14]- [18]. Antiviral therapy and/or corticosteroids have been shown to improve the prognosis in adult patients with idiopathic facial nerve palsy [19], but studies in children are few and not conclusive [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In children, infectious causes of PFP may be varied such as herpes simplex virus 1 and 2, varicella-zoster virus, human herpesvirus 6, Mycoplasma pneumoniae, Borrelia burgdorferi, influenza A and B virus, picorna, cytomegalovirus, parainfluenza virus, respiratory syncytial virus, coxsackie B5 virus, adenovirus, enterovirus, Chlamydia psittaci, and Toxoplasma gondii. 7 In the study conducted by Kanerva et al, the most frequent cause of PFP in children was Borrelia burgdorferi infection, followed in decreasing order by infection with varicella zoster virus (with or without concomitant adenovirus infection), influenza A, herpes simplex virus 1, human herpesvirus 6, and Mycoplasma pneumoniae. 7 Lip pursing in patients with PFP is performed by the asymmetrical contraction of the orbicular muscle of the lips and perioral muscles, with the traction of the anatomical myofacial structures to the unaffected side.…”
Section: Introductionmentioning
confidence: 96%
“…7 In the study conducted by Kanerva et al, the most frequent cause of PFP in children was Borrelia burgdorferi infection, followed in decreasing order by infection with varicella zoster virus (with or without concomitant adenovirus infection), influenza A, herpes simplex virus 1, human herpesvirus 6, and Mycoplasma pneumoniae. 7 Lip pursing in patients with PFP is performed by the asymmetrical contraction of the orbicular muscle of the lips and perioral muscles, with the traction of the anatomical myofacial structures to the unaffected side. For the evaluation of lip incompetence, different devices were designed, which were inserted in the buccal vestibule and tractioned, such as the Ulmer oral screen or the rigid acrylic vestibular plates.…”
Section: Introductionmentioning
confidence: 96%
“…Bell's palsy is an acute peripheral facial paralysis of unknown cause, with an annual incidence of 11–40 per 100 000 . Its cause remains unknown, although the findings of many studies have suggested that it is primarily due to viral infection, including infection with herpes simplex (HSV), Epstein–Barr and varicella zoster viruses . In particular, the detection of HSV in the human geniculate ganglion and of the HSV genome in endoneurial fluid in Bell's palsy patients strongly suggests that infection with HSV can cause Bell's palsy .…”
Section: Introductionmentioning
confidence: 99%